Ari Kuswandari, Feby Khairunisa PERENCANAAN MANAJEMEN KONSTRUKSI PADA PEMBANGUNAN GEDUNG 5 LANTAI DI JALAN HOS COKROAMINOTO KOTA PONTIANAK - Khairunisa, Feby; Kuswandari, Ari; Utomo, satriyo; Sasongko, Hartanto Wahyu (Jurusan Teknik Sipil Polnep, 2024)
Building planning is very influential because it will produce a building that meets the requirements of being sturdy, economical and aesthetic in order to avoid building damage. Construction management is a very appropriate solution for planning cost, quality, time, and Human Resources (HR) as well as Occupational Safety and Health (K3) requirements. In management planning for a 5-storey shop building in Pontianak City, an analysis of the working drawings used as the object of management planning is carried out. So that job descriptions are obtained from working drawings to analyze cost management, quality management, time management by making a Time Schedule and S Curve, human resource management, and occupational health safety. In writing this Final Project the writer uses data sources in the form of primary data and secondary data. Based on the processed data, the final results include a Budget Plan (RAB) of Rp. 2,585,448,000, the duration of the work was 24 weeks or 144 days, the project quality management made a quality checklist recapitulation in accordance with the standards, Human Resources (HR) obtained the results of the highest number of workers in the floor plate reinforcement work as many as 41 workers. Occupational Safety and Health (K3) obtained the results of risk control and the need for personal protective equipment that is in accordance with standards and requirements. Keywords: Cost, K3, Quality, Worker, Time